2017
DOI: 10.1101/165175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

unitas: the universal tool for annotation of small RNAs

Abstract: Background: Next generation sequencing is a key technique in small RNA biology research that has led to the discovery of functionally different classes of small non-coding RNAs in the past years. However, reliable annotation of the extensive amounts of small non-coding RNA data produced by high-throughput sequencing is time-consuming and requires robust bioinformatics expertise. Moreover, existing tools have a number of shortcomings including a lack of sensitivity under certain conditions, limited number of su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…In general, mapped percentage is more than 95%. Unitas v.1.5.1 (with SeqMap v1.0.13) (Gebert et al, 2017; Jiang and Wong, 2008) was used for miRNA abundance quantification with setting –species_miR_only –species mus_musculus to map the reads to mouse sequence of miRBase Release 22 (Kozomara et al, 2019). This setting (equivalent to –tail 2 –intmod 1 –mismatch 1 –insdel 0) will allow 2 non-templated 3’ nucleotides and 1 internal mismatch for miRNA mapping.…”
Section: Methodsmentioning
confidence: 99%
“…In general, mapped percentage is more than 95%. Unitas v.1.5.1 (with SeqMap v1.0.13) (Gebert et al, 2017; Jiang and Wong, 2008) was used for miRNA abundance quantification with setting –species_miR_only –species mus_musculus to map the reads to mouse sequence of miRBase Release 22 (Kozomara et al, 2019). This setting (equivalent to –tail 2 –intmod 1 –mismatch 1 –insdel 0) will allow 2 non-templated 3’ nucleotides and 1 internal mismatch for miRNA mapping.…”
Section: Methodsmentioning
confidence: 99%
“…Total number of mapped reads and percentage of mapping is summarized in Table S1. To quantify small RNAs, unitas v1.7.3 [105] (with SeqMap v1.0.13 [106]) was used to map the reads to mouse sequence of miRBase Release 22 [107], genomic tRNA database [108], Ensembl Release 96 and SILVA rRNA database Release 132. Unitas setting (-species_miR_only -species mus_musculus) was used.…”
Section: Resultsmentioning
confidence: 99%
“…We further observed a smaller fraction of RNAs in the range of 24-29 nt in both probes (Figure 2A). sRNA sequence annotation with unitas (Gebert et al 2017) revealed a similar proportion of different sRNA classes in the two probes, with miRNAs accounting for 46% and 51% of reads in the reproductive tract and muscle, respectively ( Figure 2B). Interestingly, we ascertained a substantial difference considering the abundance of tRNA fragments (tRFs).…”
Section: Pirnas In Lymnaea Stagnalis Muscle and Reproductive Tractmentioning
confidence: 88%